Adsorption and co-adsorption mechanisms of p-nitrophenol and Pb(ii) on magnetic carbon aerogel in water. Issue 4 (16th February 2022) - Liu, Jingxin; Chen, Min; Sheng, Jialing; Xu, Jiangyan; Shi, Yin; Jiang, Hongmei
Abstract : Based on adsorption and co-adsorption mechanisms of PNP and Pb(ii ), MCA without competitive adsorption has been fabricated and applied for the removal of analytes. The effect of the Fe content on magnetic and adsorption performance has been studied. Abstract : In this research, a new magnetic carbon aerogel (MCA) was successfully synthesized by the combination of a sol–gel method with the impregnation method using a resorcinol–formaldehyde (RF) gel as the carbon source and Fe 3+ as a magnetic precursor and was applied for simultaneous removal of p -nitrophenol (PNP) and Pb(ii ) in water. The effects of the contents of Fe on the morphology, structure, magnetic performance and adsorption capacity have been investigated in detail. The adsorption and co-adsorption of PNP and Pb(ii ) by 10% Fe-MCA were evaluated and the results indicate that there is no competitive adsorption between them. The maximum adsorption capacity of PNP by 10% Fe-MCA is about 141 mg g −1 and that of Pb(ii ) is about 68 mg g −1, and the co-adsorption capacity of PNP and Pb(ii ) by 10% Fe-MCA is the same as the single adsorption capacity of them. The adsorption process of PNP by 10% Fe-MCA conforms to the pseudo-second-order kinetic equation and Freundlich isothermal adsorption model; the adsorption process of Pb(ii ) conforms to the pseudo-second-order kinetic model and Freundlich isothermal adsorption equation. The adsorption mechanism of PNP by 10% Fe-MCA includes coordination between Fe from MCA and O from PNP, and hydrogen bonding. The adsorption mechanism of Pb(ii ) by 10% Fe-MCA involves coordination between Pb(ii ) and O from MCA and electrostatic attraction. The co-adsorption mechanism involves coordination between hydroxyl groups of PNP and Fe of MCA, and electrostatic attraction between the complex ions of Pb 2+ and –OH and MCA. Besides, 10% Fe-MCA can be regenerated effectively and recycled and can remove PNP and Pb(ii ) simultaneously from real water samples. These results suggest that 10% Fe-MCA can be applied to the treatment of wastewater containing both PNP and Pb(ii ).